Otimização dos parâmetros de fundição via solidificação direcional na obtenção de ligas metálicas complexas quasicristalinas de base alumínio - Barros, Thayza Pacheco dos Santos (2019)
The development of manufacturing processes that combine low cost and efficiency in the production of complex quasicrystalline metal alloys has become a challenge for researchers and engineers in order to make their production viable in industrial applications. The quasicrystalline alloys have unique microstructural characteristics and differentiated properties that make them candidates for potential uses in coatings and composites of ductile matrixes, catalysts, among others. Despite the special characteristics of these alloys, coupled with the low cost of the raw materials, the metallurgy to obtain them needs adequate processing conditions. Several conventional manufacturing techniques are used to obtain quasicrystalline alloys, such as: conventional casting in induction furnace, fast cooling casting, powder metallurgy, among others. Manufacturing processes using fast cooling showed to be efficient in the production of these materials with a higher fraction of quasicrystalline phases, already in the first stage of processing. Most of these techniques, however, present as major drawbacks high costs for large-scale production. In this sense, it is proposed a smelter processing route via unidirectional solidification, whereby the severity of the cooling can be increased in order to maximize the quasicrystalline phase amount. For this purpose, the alloy with nominal composition Al62.5Cu25Fe12.5 was unidirectionally fused and solidified under optimized processing conditions, it was possible to produce an alloy with more than 70% quasicrystalline phase, still in the melting stage. With the heat treatment of homogenization by 750 ° C / 2h, it was possible to produce 500g of alloy with more than 90% of quasicrystalline phase. This result was efficient when compared to already established techniques of use. It was possible, at the end of the work, to create an efficient route, with optimized processing conditions, for the production of quasicrystalline alloys practically homogeneous, with great prospect of large-scale production.